Sport-Related Concussion in Youth and Adult Athletes: A Narrative Review of Long-Term Outcomes and Prevention - Szczerba, Mateusz; Hejnosz, Aleksandra; Piątek, Maja; Jastrzębski, Michał; Knysak, Karol; Maj, Alicja; Wilkowska, Krystyna; Kaczorowski, Wojciech; Michałowski, Maciej Karol; Sudomir, Maria (Quality in Sport, 2026)
Sport-related concussion (SRC) is a common form of mild traumatic brain injury and represents a growing public health concern across youth, adolescent, and adult athletic populations. Characterized by transient neurological dysfunction following biomechanical forces to the head or body, SRC presents with a broad range of cognitive, physical, and emotional symptoms and is frequently underrecognized and underreported. This narrative review synthesizes current evidence on the epidemiology, risk factors, long-term neurocognitive outcomes, and prevention strategies associated with sport-related concussion. Available data indicate that SRC accounts for a substantial proportion of injuries in contact and collision sports, with particularly high incidence among youth and adolescent athletes. Younger individuals appear more vulnerable to prolonged recovery and persistent neurocognitive impairment, likely related to ongoing brain development and biomechanical factors. A history of prior concussion consistently emerges as a major risk factor for subsequent injury and adverse long-term outcomes, with cumulative exposure linked to persistent cognitive deficits and increased risk of later-life mental health disorders. Importantly, growing evidence suggests that neurocognitive impairments may persist beyond clinical symptom resolution, challenging traditional symptom-based return-to-play approaches. Effective prevention of SRC requires a multifaceted strategy. Protective equipment alone is insufficient, while standardized equipment fitting, rule modifications, consistent enforcement, education, and neuromuscular training programs show promise in reducing concussion risk. Coordinated efforts across clinical practice, sport policy, and education are essential to improve concussion recognition, management, and long-term neurological health in athletes.